Laparoscopic Management of Ectopic Pregnancy at Birat Medical College & Teaching Hospital, Morang, Nepal - Neupane, Bhanubhakta; Karki, GMS; Dahal, P; Karki, SB (Birat Journal of Health Sciences, 2017)
IntroductionEctopic pregnancy is the most life threatening emergency in first trimester of pregnancy. Laparoscopic methods for treating ectopic pregnancy have made it preferred surgical technique over laparotomy. Most of the ectopic pregnancies can now be treated by laparoscopy.ObjectiveTo study outcome of laparoscopic management of ectopic pregnancy. MethodologyA hospital based cross-sectional study was conducted at Birat Medical College and Teaching hospital from May 2013 to April 2016. The informed consent was taken from patients. The collected data was entered in Microsoft Excel and analyzed SPSS.ResultsAll 89 cases of ectopic pregnancies were managed by laparoscopy. All were tubal pregnancies. Salpingectomy was done in 88 cases and salpingostomy in one case without any significant postoperative complications. There was no maternal mortality and no conversion to laparotomy  ConclusionTreatment of ectopic pregnancy by laparoscopy is effective with decreased postoperative morbidity.Birat Journal of Health Sciences Vol.2/No.1/Issue 2/ Jan - April 2017, page: 106-109